Training needs of professionals in arts and socio-educational institutions in inclusive contexts - Pérez Romero, Antonio; Lázaro-Visa, Susana; Badia Martín, Mar; Fernández-Fuertes, Andrés A. (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2023)
The effective inclusion and participation of people with functional diversity in the cultural and artistic sphere is a pending issue. The training of professionals who develop and implement artistic and cultural projects could be an aspect to be improved; however, there are not many studies on the subject. Therefore, the aim of this research is to consider the self-perception of competences related to artistic projects of these professionals, their training needs in this area and their preferences for different training modes. To this end (To achieve that) the information was collected from 102 professionals who were selected incidentally from 17 educational, artistic and/or cultural institutions in Cantabria and Catalonia, by means of a questionnaire, interview or discussion groups. The results of this study provide the basis for the statements as follows. Firstly, the self-perception of competences is not bad, but there is much space for improvement. Secondly, the training needs are identified as diverse, but nevertheless, they seem to concentrate on either the promotion of the people’s active participation or the knowledge needed for design and implementation of real projects for all. And thirdly, a blended learning format is advocated for training in this area. Hence, the obtained data highlights the need to improve the educational specialists’ training as well as artistic and cultural spaces through interdisciplinary and cross-disciplinary initiatives that promote networking.